간호대학생 인성교육을 위한 고전읽기 프로그램 개발과 적용가능성 탐색 - 김복자(Bog-Ja Kim); 전은영(Eunyoung Jeon) (한국콘텐츠학회 논문지, 16(10), 2016)
This study explored the development and applicability of a classics book reading program in the nursing curriculum as a character education program in order to enhance nursing students' holistic growth and development. An increasing number of universities in Seoul have introduced a classics book reading program as part of the curriculum and some have even designated it as an essential subject. Various such programs have been developed in addition to the regular education curriculum. The following aspects are important to consider in a classics book reading program for nursing students: trust, respect, responsibility, fairness, caring, citizenship, endurance, healthy self-concept, and self-sustained growth performance. Classics book selections need to take into account the level of the students, and the efforts should be made to ensure the accuracy of the translation and the level of students' understanding. It is difficult to form character through short-term education. Despite difficulties, character formation requires continued interest and systemic education that will lead nursing students to show inbuilt positive characteristics. Inclusion of character education in the nursing curriculum should be considered with the agreement of the university, based on political decision-making. 본 연구는 간호대학생의 전인적인 성장과 발달에 기여할 수 있는 인성교육의 일환으로 고전읽기 프로그램을 개발하고, 이를 간호대학 교육의 한 축으로 삼아 실제로 운영할 수 있는 적용가능성을 탐색하고자 시도되었다. 우리나라의 경우 최근 서울지역 대학교를 중심으로 고전강좌가 개설되거나 필수과목으로 전환되고 있다. 각 대학은 정규교양 교과목 운영 이외에 다양한 프로그램을 개발하고 있다. 간호교육에서 인성교육을 위한 고전읽기 프로그램을 개발할 때 중요하게 다루어야 할 덕목은 신용, 존중, 책임감, 공정, 배려, 시민정신, 지구력, 건강한 자아개념, 지속적이고 자기성장능력을 포괄적으로 다루는 것이 필요하다. 고전 선정은 각 대학의 학생수준에 적합하고 함양해야할 덕목을 중점으로 정확하고도 이해하기 쉽게 번역된 도서를 선정해야 한다. 인성이 단기간의 교육을 통해 형성되기는 어렵더라도 계속적인 관심과 교육을 통하여 긍정적인 방향으로 이끌거나 내재된 긍정적 인성이 표출될 수 있도록 도울 수 있으므로 간호대학교육에서의 인성교육은 체계적으로 이루어져야 한다. 이러한 교육을 시행함에 있어서 현재의 교과과정에 대해 검토가 이뤄져야 하므로 이에 대한 대학의 합의와 고도의 정책적인 결단이 요구된다.